Penggunaan TPR dalam Pengajaran Bahasa Inggris di TK PL Kartini Semarang - Suwarti, Tarcisia Sri; Widiyanto, Muhammad Wahyu (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
Mastery of English in early childhood can be obtained from direct and indirect interactions, but if it is difficult to convey orally then it can be shown by action. At the kindergarten level of education, the role of the teacher is very important to apply language learning methods, so that students can capture and understand the teaching given. The Total Physical Response (TPR) method is very suitable for English language learning in early childhood. The problem studied refers to the formulation of the problem as follows:Â  1) How does the teacher of TK PL Kartini Semarang implement English learning with TPR method for the students? 2) How do the students respond English learning using TPR? 3) What obstacles are faced by the teachers of TK PL Kartini Semarang when they use TPR? The research method is descriptive qualitative. The subjects of the research include the teachers and students of TK PL Kartini Semarang. The conclusion of this research activity are: 1) Total Physical Response can be used to introduce vocabulary and simple instructions in English through movement and expression from the teacher; 2) Students of TK PL Kartini Semarang feel enthusiastic and happy in learning English vocabulary and instructions because they can express and do a lot of movements; 3) The obstacle faced by teachers of TK PL Kartini Semarang in the use of TPR is some instructions that need position change of the students make the class so rowdy so that teachers need extra monitoring toward student activities.